Effects of an acute strawberry (Fragaria × ananassa) consumption on the plasma antioxidant status of healthy subjects - Romandini, S.; Mazzoni, L.; Giampieri, F.; Tulipani, S.; Gasparrini, M.; Forbes-Hernandez, T.Y.; Locorotondo, N.; D'Alessandro, M.; Mezzetti, B.; Bompadre, S.; Alvarez-Suarez, J.M. (Journal of berry research, 2013)
BACKGROUND: Berries are raising increasing interest in the last years because of their nutritional quality and the several bioactive compounds with antioxidant properties that contain. Many studies reported significant increases in the plasma antioxidant capacity after long term and acute consumptions of antioxidant-rich foods. OBJECTIVE: The aim of this work was to confirm the healthy effect of strawberry consumption, evaluating the impact of an acute strawberry intake for 15 days on the plasma oxidative status of healthy volunteers. METHODS: To investigate the possible changes in the total antioxidant capacity of plasma, TEAC, FRAP, BAP and –SHp tests were performed; furthermore, the proteins' carbonyl residues test and the d-ROMs test were conducted to evaluate the protection provided by the strawberry consumption against radical damage. RESULTS: Acute strawberry consumption improved the plasma TAC, increasing FRAP and BAP values, both immediately after the strawberry consumption and the washout period. Similarly, the strawberry intake decreased proteins' carbonyl residues and d-ROMs test values. CONCLUSIONS: This study confirms the nutritional quality of Alba strawberry cultivar and demonstrates that the acute strawberry intake improves the plasma antioxidant capacity, and protects plasma proteins from the radical damage, also after the washout period.